Study on the effects of corrosion on steel arch bridges - Nur Hasna Syazana, Mohd Zaberi; Nor Ashikin, Muhamad Khairussaleh; Shariza, Mat Aris (UKM Press, 2025)
When steel is exposed to its surroundings and reacts with them, corrosion becomes one of the problems that steel bridges face. As it weakens and increases the likelihood of failure, corrosion is a concern to steel structures. Bridge fatigue life may be severely impacted by the resulting stress, which might end in catastrophic failure. The appearance and spread of fatigue cracks can be accelerated by corrosion, which causes the steel structure to deteriorate more quickly. Visual examinations frequently identify corrosion quickly, but a thorough assessment and study of corrosion damage are crucial. This research focuses on analysing the behaviour of a steel arch bridge under the influence of corrosion that occurs at the bridge. The study aims to determine the different stress levels resulting from corrosion. By employing SAP2000 software, three corrosion levels with 10%, 20%, and 50% of the selected section area at the bridge’s centre span and abutment are considered by reducing the structure’s cross-sectional area. Stress values are obtained by considering the most probable location of corrosion. The results and discussion reveal that steel arch bridges exhibit excellent flexibility and deformation. Segment of the bridge that located at the centre, experienced the highest stress range and potential concentrations. These finding underscore the importance of effective corrosion prevention and maintenance strategies. It is crucial to ensure their long-term durability and structural integrity.